1987
DOI: 10.1038/328527a0
|View full text |Cite
|
Sign up to set email alerts
|

A linked genetic marker for multiple endocrine neoplasia type 2A on chromosome 10

Abstract: Multiple endocrine neoplasia type 2A (MEN2A) is an autosomal dominantly inherited cancer syndrome characterized by medullary carcinoma of the thyroid, phaeochromocytoma and hyperparathyroidism. Almost all gene carriers can be detected by screening tests before the age of 40, but the nature and location of the predisposing gene are unknown. Simpson et al. recently reported preliminary evidence for linkage between the DNA probe p9-12A on chromosome 10 and MEN2A. We now report linkage between the MEN2A locus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
10

Year Published

1989
1989
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(107 citation statements)
references
References 0 publications
2
95
0
10
Order By: Relevance
“…Both RBP3 and FNRB are linked to the MEN-2A locus, and the MEN2A locus lies between these markers (Meyers et aI., 1989). The linkage data analyzed from Japanese MEN 2A families is consistent with that ef European Caucasian kindreds (Mathew et al, 1987;Simpson et al, 1987;Yamamoto et al, 1989;Meyers et al, 1989). The recombination fraction (Om=Of) at maximum lod scores between MEN2A and these markers is calculated to be 0.045. for RI~P3 (Zm,x=13.t), and 0.063 for FNRB (Zm~x=13.2) (Wu et al, 1990), respectively.…”
Section: Discussionsupporting
confidence: 77%
“…Both RBP3 and FNRB are linked to the MEN-2A locus, and the MEN2A locus lies between these markers (Meyers et aI., 1989). The linkage data analyzed from Japanese MEN 2A families is consistent with that ef European Caucasian kindreds (Mathew et al, 1987;Simpson et al, 1987;Yamamoto et al, 1989;Meyers et al, 1989). The recombination fraction (Om=Of) at maximum lod scores between MEN2A and these markers is calculated to be 0.045. for RI~P3 (Zm,x=13.t), and 0.063 for FNRB (Zm~x=13.2) (Wu et al, 1990), respectively.…”
Section: Discussionsupporting
confidence: 77%
“…[2][3][4] In 1987, Mathew et al 5 linked the gene to the pericentromeric region of chromosome 10, and in 1993, it was demonstrated that mutations in the RET protooncogene were associated with the inherited form of MTC, 6,7 occurring first in MEN 2A and FMTC.…”
mentioning
confidence: 99%
“…In cases in which it was examined, these deletions were not noted in the constitutional (normal) DNA of the patients, indicating that the deletion does not reflect the site of the inherited mutation. LOH has been noted on other chromosomes also, including 3p, l lp, 17p, and chromosome 22q, but LOH for lp has been the most consistent finding to date (Khosla et al,1991;Mathew et al, 1987b;Moley et al, 1992;Takai et al, 1987;Tsutsumi et al, 1989;Yang et al, 1990). This suggests that an important suppressor gene resides on this chromosomal arm, and its loss or inactivation plays a role in the development or progression of pheochromocytomas, at least in a substantial subset of patients.…”
Section: Loss Of Heterozygosity and Mapping Of Putative Suppressor Genesmentioning
confidence: 98%
“…Several studies using polymorphic -probes for the short arm of chromosome 1 have noted LOH involving 1 p in about half the cases studied (Khosla et al, 1991;Mathew et al, 1987b;Moley et al, 1992;Takai et al, 1987;Tsutsumi et al, 1989;Yang et al, 1990). In cases in which it was examined, these deletions were not noted in the constitutional (normal) DNA of the patients, indicating that the deletion does not reflect the site of the inherited mutation.…”
Section: Loss Of Heterozygosity and Mapping Of Putative Suppressor Genesmentioning
confidence: 99%